EFFECT OF PGPR AND ORGANIC MANURES ON SOIL PROPERTIES OF ORGANICALLY CULTIVATED MUNGBEAN - DAS, IPSITA; A. P. SINGH (The Bioscan, 2013)
A field experiment was undertaken in the organic farming plot of the Institute of Agricultural Sciences, BHU, Varanasi with a view to study the effects of manures and PGPR on soil properties. Mungbean (var. Malviya 12) was grown in the plot during kharif season of 2009. Organic manures such as Farm yard manure (FYM), Cereal compost, Legume compost and combination of all the manures with or without PGPR [PGPR: Plant Growth Promoting Rhizobacteria containing Rhizobium + Azotobacter + Pseudomonas + Trichoderma] was applied @ 5 t ha-1 in each plot. It was found that among all the manures tested for cultivation of mungbean, FYM was found to be superior having 320.91, 20.3, 286.72 kg ha-1 N, P2O5 and K2O respectively. The combined application of cereal compost and legume compost was effective over their sole application. Application of PGPR was beneficial showing higher nutrient content in soil. The most effective treatment was found to be FYM + PGPR among all the manures showing the highest amount of nutrients of 339.71, 22.33 and 298.66 kg ha-1 N, P2O5 and K2O respectively.